Identification of prognostic DNA methylation biomarkers in patients with gastrointestinal adenocarcinomas: A systematic review of epigenome-wide studies - d'Errico, Margherita; Alwers, Elizabeth; Zhang, Yan; Edelmann, Dominic; Brenner, Hermann; Hoffmeister, Michael (Cancer treatment reviews, 2020)
This systematic review aims to summarize epigenome-wide studies on aberrant DNA methylation and its association with survival in patients with gastrointestinal adenocarcinoma. The 15 studies identified showed a large variety of methodological approaches for the identification of prognostic epigenetic markers from genome-wide methylation analyses. None of the findings were reported by more than one study in this systematic review. Further validation studies, a better reporting of methods and results are needed, as well as a clearer definition of investigated outcomes. At present, no conclusions can be drawn on the clinical relevance of the reported epigenetic markers.
Available online 23 November 2019
Gesehen am 26.03.2020